Methods for analysis of carbohydrate metabolism in photosynthetic organisms : plants, green algae and cyanobacteria - Pontis, Horacio G. (London : Academic Press, 2016)
Methods for Analysis of Carbohydrate Metabolism in Photosynthetic Organisms: Plants, Green Algae and Cyanobacteria examines both general and detailed aspects of carbohydrate metabolism in photosynthetic organisms, along with the four main oligosaccharides and each enzymatic reaction that gives birth to them. Chapters include information on how biological active protein is extracted for different cells, determination of enzymatic activity, separation of proteins by different available methods, and descriptions of analytical methods for the determination of various types of carbohydrates in photosynthetic organisms. The book contains useful protocols for researchers working on the determination of carbohydrate metabolism. The book provides foundational content as well as step-by-step guidance on how to design and conduct an experiment, including what other methodologies could be used if advanced instruments are not readily available. Includes a variety of analytical methods and how to apply the methods using examples from specific case studies Discusses technical information on how to characterize plant carbohydrates and sugar nucleosides Contains easy-to-follow protocols with detailed explanations for self-guidance Provides foundational content as well as step-by-step guidance on how to design and conduct an experiment.
2.3.2.2 Preparation of protein extracts from spinach and Arabidopsis chloroplasts2.3.3 Preparation of Extracts from Photosynthetic Microorganisms; 2.3.3.1 Chlorella vulgaris; 2.3.3.2 Chlamydomonas reinhardtii; 2.3.3.3 Ostreococcus tauri; 2.3.3.4 Cyanobacteria; 2.4 Protein Extract Desalting; Further Reading and References; 3 Protein and Carbohydrate Separation and Purification; 3.1 Introduction; 3.2 Enzymatic Protein Purification; 3.2.1 Methods Based on Protein Solubility; 3.2.2 Protein Fractionation by Batch Adsorption; 3.2.3 Protein Fractionation by Chromatographic Techniques.
Print version record.
Includes index.
Keywords: Carbohydrates -- Metabolism; Photosynthates; SCIENCE -- Life Sciences -- Biochemistry; Carbohydrates -- Metabolism; Photosynthates; Electronic books